Development of sorghum plants submitted under different water table levels in glasshouse - Tanaka, Adriana Aki [UNESP] (2014)
This study aimed to evaluate the sorghum plants development (Sorghum bicolor L. Moench) submitted to different water table levels. The experiment was carried out in a glasshouse on trays with water reservoirs that allowed sub irrigation, and PVC tubes (15 cm diameter) with different heights simulating five water table levels (17 cm; 31 cm; 45 cm; 59 cm; 73 cm), treatments T1; T2; T3; T4; T5 respectively, in an entirely random design. The analyzed parameters were: fresh and dry matter, height and stem diameter of plants; fresh and dry matter and length of panicles; dry matter of roots; leaf area; crop evapotranspiration (ETc), and Kc= ETc/ETo. Water table depths between 45 and 59 cm showed significantly higher values for fresh and dry matter. The weight for fresh and dry matter and length of panicle tended to higher values for T4 and T5. There was no statistical significance among T3, T4 and T5 for stem diameter. Cultivated plants under water table closer to the surface induced plants to produce thicker stems.